2022
DOI: 10.21776/ub.jam.2022.020.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Telework, Well-Being, Stress, and Productivity During Covid-19 Pandemic: Does Women's Resilience Matter?

Abstract: This study aims to analyze the relationship between perceived stress, psychological well-being and perceived productivity through teleworking with resilience as moderation for married female employees in the telecommunications network company in Jakarta. The data analysis method used was Structural Equation Modeling (SEM)–Partial Least Square (PLS) by distributing questionnaires to 148 married women employees. Data were collected from December 2021 to 2022 through an online questionnaire distributed through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
1
Order By: Relevance
“…However, in this study, it was also found that remote working does not moderate the correlation between employee engagement and employee creativity in the tourism service industry (Anindita & Korompis, 2022) This signifies that good remote working does not strengthen the correlation between employee engagement and employee creativity. This result contradicts the hypothesis and is not in line with the results of a study carried out by (Vithayaporn & Ashton, 2019).…”
Section: Discussioncontrasting
confidence: 64%
“…However, in this study, it was also found that remote working does not moderate the correlation between employee engagement and employee creativity in the tourism service industry (Anindita & Korompis, 2022) This signifies that good remote working does not strengthen the correlation between employee engagement and employee creativity. This result contradicts the hypothesis and is not in line with the results of a study carried out by (Vithayaporn & Ashton, 2019).…”
Section: Discussioncontrasting
confidence: 64%
“…The more positive the perception of organizational support for employees, the higher their well-being will be (Dini and Mubarak, 2021). Employees in this era need some support to fulfill their responsibilities at work because lack of support will impacts their well-being (Anindita and Korompis, 2022). H1: Perceived organizational support positively and significantly impacts the subjective well-being of permanent employees and temporary employees in the hybrid workforce era.…”
Section: Methodsmentioning
confidence: 99%